Development and study of conducting materials for H2O2 and glucose sensors / Tilagam a/p Marimuthu - Marimuthu, Tilagam (2015)

(untitled)
This thesis originated with the development and characterisation of composite materials for sensor applications. This study focused on conducting polymer-metal oxide based composites and silica-titania oxide based composites. The conducting polymer-metal oxide composites were synthesised by chemical polymerisation technique with an aqueous solution of pyrrole monomer in the presence of cobalt and nickel salts. Various analytical techniques were employed to characterise these composites such as field emission scanning electron microscope-energy dispersive x-ray (FESEM-EDX), x-ray powder diffraction (XRPD), Fourier Transform Infrared (FTIR) and thermogravimetric analysis (TGA). These composites were then fabricated into chemical sensor by drop-dry electrodeposition method on glassy carbon electrode (GCE). The electrochemical response towards the modified GCE was examined using both cyclic voltammetry and chronoamperometry. The polypyrrole coated cobalt (PPy-Co)/GCE shows sensitivity towards hydrogen peroxide (H2O2). While, the polypyrrole coated nickel oxide (PPy-NiO)/GCE shows its current response towards glucose. Both PPy-Co/GCE and PPy-NiO/GCE give high response towards target analyte at optimum condition of 500 μL pyrrole monomer content. Furthermore, the presence of pyrrole monomer greatly increases the sensitivity of the respective modified electrode. The PPy-Co/GCE could detect H2O2 in a linear range of 20 μM to 80 mM with two linear segments (low and high concentration of H2O2) and the detection limit for both ranges is 2.05 μM and 19.64 μM, respectively. While, PPy-NiO/GCE exhibited good electrocatalytic oxidation towards glucose in alkaline medium and could detect glucose in linear ranges of 0.01 mM to 0.50 mM and 1 mM to 20 mM with detection limit of 0.33 μM and 5.77 μM, respectively. Besides, the Si-Ti oxide based composite was also synthesised and developed as an enzymatic sensor. This composite was synthesised by iv sol-gel method in the presence of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C4MIm][NTf2]) ionic liquid and was characterised by FTIR, TGA, XRPD, FESEM-EDX, CHN and N2 adsorption-desorption analysis. The presence of C-N groups in the FTIR spectrum indicates the presence of the ionic liquid in the Si-Ti matrix, while, the XRPD, FESEM and N2 adsorption-desorption analysis results show that the composite materials possessed good microporous characteristics. This composite was then fabricated as an enzymatic sensor by layer-by-layer drop-dry electrodeposition method onto the surface of GCE. Ferrocene (Fc) was chosen as mediator and horseradish peroxidase (HRP) was selected to detect H2O2. The electrochemical response of H2O2 towards the modified GCE was examined by using cyclic voltammetry. But, this modified Si-Ti-[C4MIm][NTf2]-HRP/Fc/GCE did not give significant electrocatalytic responses towards H2O2.